Analisa Kelayakan Pabrik Neon Elektronik (NE) Sukoharjo - Nina Lutfia; I Wayan Suletra; Fakhrina Fahma (Industrial Engineering Study Program, Faculty of Engineering, Universitas Sebelas Maret, 2004)
The increasing of electricity base rates initiate people to choose the energy saving lamp in order to decrease their electricity bill. It impacts the demand of energy saving lamps increase. Neon Electronic produces such an energy saving lamp with the electronic circuit called ballast electronic. Neon Electronic plan to develop the factory and expand the marketing area.This research is aimed to know the feasibilities of the Neon Electronic (NE) development plan. The feasibilities study covered a research on market aspects, production and operastional aspects, and financial aspects.Based on the result of market aspects, this development plan is feasible; because of the people demand. so, there is an opprtunity to implement this plan. Despite from that there is a particular interest factors such as the quality of Neon Electronic is higher than the around competitors.From the production and operational aspects, this plan is also feasible to continue because there is no barrier on the availability of the machines and tools and another production fasilities, the development fund, and human resources.With the assumption that the interest rate is 16% and all the product sold, the result of investment criteria; NPV is Rp. 167.778.623, IRR = 98% which is bigger than the interest rate, Discounted Payback Period = 1 year 3,78 months, no cash deficit, the Profitability Index above one which is 2,86, and the Break Even Point (BEP) 2004 is Rp. 307.879.319. The financial aspects point of view recommends this development plan is possible to continue.